771 Quad-related fatal injuries 2007–2012: a comparison between Australia and New Zealand. (1st September 2016) - Lilley, Rebbecca; Lower, Tony; Davie, Gabrielle; Wilson, Sue
Abstract : Background: Serious concerns have been raised over the safety of quad bikes in Australia and New Zealand (NZ). Previous studies have sought to describe quad fatalities within each country. Given the economic similarities between Australia and NZ, cross-country comparisons could untease geographical and policy influences to inform injury prevention initiatives in both countries. This presentation describes and compares the personal, injury and environmental factors associated with quad fatalities for the period 2007–2012 using Coronial case files for Australia and NZ. Methods: Coronial case files for the period 2007 to 2012 held by the National Coronial Information System, Australia were used to identify fatalities involving a quad for both Australia and NZ using key word and mechanism searches. Information on the decedent was extracted from coronial case files. The circumstances surrounding the fatal incident was coded using the Australian Farm Injury Optimal Dataset coding framework. Comparison of the distribution of decedent, injury characteristics and event circumstances were undertaken. Results: A total of 101 quad-related fatalities were identified: 69 in Australia and 32 in NZ. The pattern of decedent characteristics was similar between both countries. Month of incident differed with 63% of Australian fatalities occurring January-June, while 66% of NZ fatalities occurred July-December. Differences where observed for primary mechanism of injury with Australian fatalities mainly involving collisions with stationary objects while NZ fatalities mainly involved quad roll-over. The presence of a slope was more commonly observed in NZ quad-related fatalities. Conclusions: Given patterns of quad-related fatalities are similar between Australia and NZ consolidation of injury prevention initiatives, particularly around quad manufacturing standards and controls, could be undertaken to develop effective prevention interventions to address commonly held quad safety concerns.